2022
DOI: 10.3390/agriculture12070928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vertical Smashing Rotary Tillage on Root Growth Characteristics and Yield of Broccoli

Abstract: Most of the soils of the cultivated land in southern China are Ferralsols, which are easily deposited and hardened. To date, rotary tillage (RT) has been the major tillage system used in China. This tillage system results in a shallow soil pan, which reduces broccoli growth and yield. A two-year field experiment was conducted in the Central Zhejiang Basin, China, to compare the effects of vertical smashing rotary tillage (VSRT), RT, and vertical rotary tillage (VRT) on the soil properties, growth characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Reduced soil water infiltration might result in more runoff and erosion from sloping land or flooded soils in flat places. Crop yields are decreased by shallow plant roots and poor plant growth, brought on by a high bulk density [36]. BD increased with depth, due to the influence of SOM that affects soil structure [37].…”
Section: Effects Of Selected Smcps On Selected Soil Propertiesmentioning
confidence: 99%
“…Reduced soil water infiltration might result in more runoff and erosion from sloping land or flooded soils in flat places. Crop yields are decreased by shallow plant roots and poor plant growth, brought on by a high bulk density [36]. BD increased with depth, due to the influence of SOM that affects soil structure [37].…”
Section: Effects Of Selected Smcps On Selected Soil Propertiesmentioning
confidence: 99%
“…Root growth is strongly limited by the soil environment; increased root hair proliferation, root length, and root number have been observed in loosed soil conditions [54]. FT deep tillage breaks the hardpan under the plow layer and up to the subsoil can alleviate root entry pressure, thus increasing the rooting depth, water, and nutrient uptake [17,44,67,68]. Li et al [20] found that FT resulted in more sugarcane root hairs and increased root length and density compared with conventional tillage.…”
Section: Ft Integrated With Biochar and Fertilization Improve Sugarca...mentioning
confidence: 99%
“…Its primary advantage over traditional methods is its ability to deeply loosen the soil without disturbing its layers [10]. Following deep vertical rotary tillage, the arable layer becomes crushed, loosened, and granular, promoting improved ventilation, soil permeability, and water retention [21]. This technology revolutionizes dry land cultivation by adopting interval deep rotary tillage planting, creating a "U" shaped groove that effectively utilizes soil resources and natural precipitation below the tillage layer, expanding space for soil water storage and fertilizer retention [22].…”
Section: Introductionmentioning
confidence: 99%